Influence of pelvic floor disorders on quality of life in women - Peinado Molina, Rocío Adriana; Hernández Martínez, Antonio; Martínez Vázquez, Sergio; Martínez Galiano, Juan Miguel (Frontiers in Public Health, 2023)
Objective: To determine whether the different pelvic floor disorders are associated with changes in perceived quality of life (QoL), globally and in its sub-dimensions. Methods: An observational study was conducted with women in Spain between 2021 and 2022. Information was collected using a self-developed questionnaire on sociodemographic data, employment, history and health status, lifestyle and habits, obstetric history, and health problems. The SF-12 questionnaire was used to assess quality of life. The Pelvic Floor Distress Inventory (PFDI-20) was used to assess the presence and impact of pelvic floor problems, and includes the POPDI-6 subscales for prolapse, CRADI- 8 for colorectal symptoms, and UDI-6 for urinary symptoms. Crude (MD) and adjusted mean differences (aMD) were estimated with their respective 95% confidence intervals (CI). Results: 1446 women participated in the study with a mean age of 44.27 (SD= 14.68). A statistical association was observed between all the pelvic floor disorders and QoL, overall and in all its dimensions (p<0.001), in the bivariable analysis. The lowest scores were observed in the emotional component. After adjusting for confounding factors, the pelvic floor disorders in general (aMD -0.21, 95% CI: -2.73 to -2.28), the impact of uterine prolapse symptoms (aMD -0.20, 95% CI: -0.27 to -0.12), the colorectal-anal symptoms (aMD -0.15, 95% CI: -0.22 to -0.09), and urinary symptoms (aMD -0.07, 95% CI: -0.13 to -0.03) was negatively associated on the score on the SF-12 questionnaire (p<0.05). Conclusions: Women who have a pelvic floor dysfunction, symptoms of pelvic organ prolapse, colorectal-anal symptoms, or urinary symptoms, have a worse perceived quality of life in all dimensions. Prolapse symptoms have the biggest impact, and the emotional component of QoL is the most affected sub-domains.